2013
DOI: 10.1021/jp3106716
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Dissolution Behavior of Naproxen/Polyethylene Glycol Solid Dispersions

Abstract: The crystallization kinetics of naproxen (NAP) in NAP/polyethylene glycol (NAP/PEG) solid dispersions prepared at different crystallization temperatures was studied by in situ small-angle X-ray scattering/wide-angle X-ray scattering (SAXS/WAXS). It was found that the crystallization rate of NAP was faster at 25 °C in comparison to 40 °C. This resulted in different sizes of NAP domains, and consequently impacted the dissolution behavior. The sizes of NAP domains prepared at 40 °C were larger than those at 25 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Recent research in inkjet printed pharmaceuticals has focused on solutions (Alomari et al, 2015;Genina et al, 2013;Scoutaris et al, 2011;Sandler et al, 2011;Raijada et al, 2013;Lee et al, 2012;Acosta-Vélez et al 2017), nanosuspensions (Pardeike et al, 2011), and melts Zhu et al, 2013), each of which is primarily 2D. Reel to reel type flexographic (Raijada et al, 2013;Palo et al, 2015) printing, as well as inkjet printing in combination with electrospinning have also been utilized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in inkjet printed pharmaceuticals has focused on solutions (Alomari et al, 2015;Genina et al, 2013;Scoutaris et al, 2011;Sandler et al, 2011;Raijada et al, 2013;Lee et al, 2012;Acosta-Vélez et al 2017), nanosuspensions (Pardeike et al, 2011), and melts Zhu et al, 2013), each of which is primarily 2D. Reel to reel type flexographic (Raijada et al, 2013;Palo et al, 2015) printing, as well as inkjet printing in combination with electrospinning have also been utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Varan et al has investigated the prolonged release behaviour of inkjet printed paxitaxel in a cyclodextrin inclusion complex and cidofovir encapsulated in polycaprolactone nanoparticles dispensed onto bioadhesive films . Low melting temperature PEG/naproxen mixtures Zhu et al, 2013;Hsu et al, 2015) have been reported for melt based inkjet applications in which crystalline domains of the drug could be affected by PEG coatings (Hsu et al, 2015), or controlled melt cooling . Lee et al successfully produced paxlitaxel loaded poly(lactic-co-glycolic acid) microparticles with various geometries (honeycombs, grids, rings and circles) and observed that the drug release rate was dependant on the surface area of the microparticles (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of model systems have suggested detection limits on the order of ppm for crystallinity within amorphous solid dispersions. 2832 …”
mentioning
confidence: 99%
“…The melt formulation consisted of 15% naproxen and 85% polyethylene glycol 3350 (PEG 3350) by weight. This formulation was selected based on the studies done by Zhu et al (2013) which showed that naproxen and PEG 3350 form a eutectic mixture at a composition of 15% naproxen (27). The formulation was co-melted at 65°C, at which temperature the polymer melts and the drug dissolved in the molten polymer.…”
Section: Resultsmentioning
confidence: 99%